Urolithins: The Gut Based Polyphenol Metabolites of Ellagitannins in Cancer Prevention, a Review - Al-Harbi, Sami A.; Abdulrahman, Abdulrasheed O.; Zamzami, Mazin A.; Khan, Mohammad Imran (Frontiers in Nutrition, 2021)
Cancer as a disease continues to ravage the world population without regard to sex, age, and race. Due to the growing number of cases worldwide, cancer exerts a significant negative impact on global health and the economy. Interestingly, chemotherapy has been used over the years as a therapeutic intervention against cancer. However, high cost, resistance, and toxic by-effects to treatment have overshadowed some of its benefits. In recent times, efforts have been ongoing in searching for anticancer therapeutics of plant origin, focusing on polyphenols. Urolithins are secondary polyphenol metabolites derived from the gut microbial action on ellagitannins and ellagic acid-rich foods such as pomegranate, berries, and nuts. Urolithins are emerging as a new class of anticancer compounds that can mediate their cancer-preventive activities through cell cycle arrest, aromatase inhibition, induction of apoptosis, tumor suppression, promotion of autophagy and senescence, transcriptional regulation of oncogenes, and growth factor receptors. In this review, we discussed the growing shreds of evidence supporting these secondary phenolic metabolites' anticancer properties. Furthermore, we have pointed out some of the future directions needed to establish urolithins as anticancer agents.